Evaluation of the Painful Total Knee Arthroplasty - Cercek, Robert; Bassett, Richard; Myerthall, Steve (The Journal of Knee Surgery, 2015)
There are a substantial number of patients who continue to complain of pain following total knee arthroplasty (TKA). There are many potential causes of continued pain, and these are broadly categorized into intrinsic and extrinsic sources. When evaluating a patient with a painful TKA, the physician begins with a thorough history and physical examination, along with the appropriate radiographs. Further workup includes laboratory analysis, specifically evaluating the inflammatory markers erythrocyte sedimentation rate and C-reactive protein, along with a synovial fluid aspirate evaluating the white blood cell count with differential and culture. Advanced imaging modalities are sometimes helpful when the diagnosis remains unclear, including stress radiographs, live fluoroscopic imaging, ultrasound, nuclear imaging, and magnetic resonance imaging. Further surgery is not advisable without a clear diagnosis, as this is associated with very poor results. Instead, serial follow-up or a referral to a specialist for a second opinion may be most appropriate.
Keywords: knee pain; total knee arthroplasty; failure